2013
DOI: 10.1177/159101991301900302
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis for Wingspan Stent in a Perforator Model

Abstract: Perforator infarction represents a critical problem after intracranial Wingspan stent. To explore the mechanism of perforator infarction, we simulated the stent-artery interaction at an atheromatous plaque with perforator. Structural deformation and biomechanical stress distribution after stenting were analyzed. High radial stress values were located along the stent struts, which surrounded the area with high circumferential stress. Stretched perforator orifice in a circumferential direction after ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In SAMMPRIS, the only randomized controlled trial (RCT) comparing the Wingspan stent and optimal drug therapy, Wingspan stent use was associated with a higher rate of perioperative complications [ 6 ]. Complex ICAS, i.e., that in tortuous vascular segments, long (>15 mm) lesions and/or arterial bifurcations, has been associated with higher rates of complications and renders particularly difficult the deployment of the Wingspan stent because of its high radial force and rigidity [ 7 , 8 ]. The self-expanding, closed-cell Enterprise stent, which was originally designed for neck remodeling in the treatment of wide-necked intracranial aneurysms [ 9 ], appears better suited than the Wingspan stent for the treatment of complex ICAS because of its high flexibility, special carrier system structure [ 10 ] and reduced radial force [ 10 ], which is nonetheless sufficient to prevent elastic recoil and restenosis.…”
Section: Introductionmentioning
confidence: 99%
“…In SAMMPRIS, the only randomized controlled trial (RCT) comparing the Wingspan stent and optimal drug therapy, Wingspan stent use was associated with a higher rate of perioperative complications [ 6 ]. Complex ICAS, i.e., that in tortuous vascular segments, long (>15 mm) lesions and/or arterial bifurcations, has been associated with higher rates of complications and renders particularly difficult the deployment of the Wingspan stent because of its high radial force and rigidity [ 7 , 8 ]. The self-expanding, closed-cell Enterprise stent, which was originally designed for neck remodeling in the treatment of wide-necked intracranial aneurysms [ 9 ], appears better suited than the Wingspan stent for the treatment of complex ICAS because of its high flexibility, special carrier system structure [ 10 ] and reduced radial force [ 10 ], which is nonetheless sufficient to prevent elastic recoil and restenosis.…”
Section: Introductionmentioning
confidence: 99%
“…The self-expanding Wingspan stent (Stryker Neurovascular, Freemont, California, USA), a dedicated stent system approved by the US FDA for patients with transient ischemic attack (TIA) or stroke secondary to stenosis of a major intracranial artery,8 9 appears structurally unsuited for treatment of complex ICAS, yielding a lower success rate in complex lesions such as long, bifurcation, or tip lesions and those with tortuous access, and a higher rate of periprocedural complications than in simple lesions 10 11…”
Section: Introductionmentioning
confidence: 99%
“…The balloon is inflated across the stenotic lesion as a long balloon is more stable during inflation and easier to keep positioned, decreasing the incidence of balloon migration. The migration of a balloon can aggravate the “snow plow” effect, which is the main mechanism of perforator stroke after intracranial stenting (23). Therefore, as for the lesion in a relatively straight vessel, a long balloon (15 mm, in general) is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…These features of the Neuroform EZ system seem to translate into lower complication rates. Some studies have demonstrated a higher technical success rate with a microcatheter delivered stent [Enterprise stent (94–100%) (3, 4, 24) Solitaire stent (100%) (25) than with Wingspan stent (91.2–100%) (1723)].…”
Section: Discussionmentioning
confidence: 99%